Improving student outcome in higher education the science of targeted intervention. - Harackiewicz, Judith M.; Priniski, Stacy J.
Many theoretically based interventions have been developed over the past two decades to improve educational outcomes in higher education. Based in social-psychological and motivation theories, well-crafted interventions have proven remarkably effective because they target specific educational problems and the processes that underlie them. In this review, we evaluate the current state of the literature on targeted interventions in higher education with an eye to emerging theoretical and conceptual questions about intervention science. We review three types of interventions, which focus on the value students perceive in academic tasks, their framing of academic challenges, and their personal values, respectively. We consider interventions that (a) target academic outcomes (e.g., grades, major or career plans, course taking, retention) in higher education, as well as the pipeline to college, and (b) have been evaluated in at least two studies. Finally, we discuss implications for intervention science moving forward. -- (from the author)
Keywords: Intervention; Achievement gaps; Belonging; Utility value; Values affirmation